PENGEMBANGAN MEDIA FLASH DALAM PEMBELAJARAN SEJARAH UNTUK PEROLEHAN BELAJAR KONSEP PERGERAKAN NASIONAL INDONESIA - Susanto, Dwi; Mering, Aloysius; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to reveal the meaning of the development of flash media through the design of flash media development in history learning for the acquisition of learning the concept of Indonesian national movement. Further, the research applies the development research method by combining the Borg & Gall development model with the Dick & Carrey learning design model. Data were obtained through interviews, observations and tests that are occurred to research subjects. The flow of the implementation of this study through three main stages, namely (1) Flash media design stage, including analysis of learning objectives, learning analysis, identifying students, formulation of special objectives, and planning of flash media; (2) Stage of product development namely flash media profiles consisting product development, test instruments, learning strategies, developing and selecting teaching materials, designing and developing evaluation drafts, Revising learning packages; trial and revision stages, containing small group trials, initial product revisions, testing medium scale, product revision of the second trial, and large scale trial. (3) the learning process with high flash media, that is, 87.8% in the teacher's activities and 83.9% in the student's activities. (4) Furthermore, learning outcomes achieved by using flash media were the increase the average of mastery learning in the implementation of pre-test and post-test, from 54.5 to 90 with the results of t test (?) of 0.05 t count of 13.86> t table of 1.729. Keywords: Flash Media Learning Result.